Effects of Metabolic Factors on Left Ventricular Diastolic Function in Patients with Obstructive Sleep Apnea - Zhou YF; Chen SH; Wang WD; Chen JL; Cai PY; Li MM; Lin YL; Li WQ; Huang DH; Li J; Li YT; Lin HL (Nature and Science of Sleep)
Yi-Fan Zhou,1,* Shu-Han Chen,1,* Wan-Da Wang,1 Jia-Le Chen,1 Ping-Yu Cai,1 Mei-Mei Li,1 Yue-Ling Lin,1 Wan-Qi Li,1 De-Hong Huang,1 Jun Li,1 Yue-Ting Li,2 Hui-Li Lin1 1Department of Cardiology, The Second Affiliated Hospital of Fujian Medical University, Quanzhou, Fujian Province, People’s Republic of China; 2Department of Nephrology, The Second Affiliated Hospital of Fujian Medical University, Quanzhou, Fujian Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hui-Li Lin, Department of Cardiology, The Second Affiliated Hospital of Fujian Medical University, No. 34 North Zhongshan Road, Quanzhou, Fujian Province, 362000, People’s Republic of China, Tel +86 18876598756, Email 1627974150@qq.com Yue-Ting Li, Department of Nephrology, The Second Affiliated Hospital of Fujian Medical University, No. 34 North Zhongshan Road, Quanzhou, Fujian Province, 362000, People’s Republic of China, Tel +86 15359593070, Email liyt163@126.comPurpose: The effect of metabolic factors on cardiovascular risk in obstructive sleep apnea (OSA) is unclear. This study aimed to investigate the effect of metabolic factors on the left ventricular diastolic function in patients with OSA.Patients and Methods: This cross-sectional study included a total of 478 patients with OSA from September 2018 to September 2023. After propensity score matching, wherein 193 patients with OSA with metabolic syndrome (MS) were 1:1 matched to patients with OSA without MS by sex and age, data from 386 patients were ultimately analyzed. Furthermore, all patients were divided into mild, moderate, and severe OSA groups according to their sleep apnea-hypopnea index (AHI). Measurements included nocturnal polysomnography, biochemical testing, and transthoracic echocardiography data.Results: The AHI in the MS group was higher (30.24± 21.69 vs 23.19± 17.65, p< 0.001) and the lowest oxygen saturation at night was lower (77.67± 9.23 vs 80.59± 9.26, p< 0.001) than those in the non-MS group. Additionally, the left ventricular end-diastolic diameter (LVEDD), left ventricular end-systolic diameter (LVESD), end-diastolic ventricular septal thickness (IVST), left ventricular end-diastolic posterior wall thickness (LVPWT), left atrial internal diameter (LAD), and E peak to A peak velocity ratio (E/A) in the MS group were higher than those in the non-MS group (P< 0.05). The E peak to e’ peak velocity ratio (E/e’) in the MS group was higher than that in the non-MS group (12.02± 3.68 vs 11.13± 3.12, P=0.011) and was positively correlated with the diagnosis of MS and metabolic factors (r=0.115, p=0.024; r=0.131, p=0.010, respectively). Patients with five metabolic factors had a significantly higher risk of E/e’ elevation than patients in the non-MS group (odds ratio=4.238, p=0.007).Conclusion: MS may be related to OSA severity and left ventricular diastolic dysfunction. An increase in metabolic factors may increase the risk of diastolic dysfunction. Among metabolic factors, blood pressure may be the most important.Keywords: metabolic syndrome, obstructive sleep apnea, left ventricular dysfunction